Hubungan Pembelajaran Daring terhadap Tingkat Stress Akademik Anak Selama Pandemi Covid 19 di SDN 2 Kedamaian Bandar Lampung - Dimas Adi Krisna; Riska Wandini; Linawati Novikasari (Universitas Malahayati Lampung, 2023)
ABSTRACT The Covid-19 pandemic in Indonesia disrupted all public events and caused the temporary closure of several institutions, including educational institutions. The government has established an online policy. Bulletin of the Minister of Education and Culture, which states that education must be carried out online to prevent the spread of covid 19. It is known the Relationship between Online Learning and children's academic stress levels during the Covid-19 pandemic at Sdn 2 Kedamaian Bandar Lampung. The type of research used is quantitative. The research design used is retrospective. The population of this research is all 3rd grade students of SDN 2 Kedamaian Bandar Lampung as many as 109 people with a total sample of 86 respondents. And for the samplin g technique used is Purposive Sampling. In this study, the questionnaire that will be used in this study is the ESSA questionnaire. This study uses univariate data analysis and bivariate data analysis. Data analysis used logistic regression test. The results of the study, it is known that respondents from 86 respondents obtained the characteristics of respondents. Based on age, the majority of respondents were 9 years old (77.9%). Based on gender, the majority of respondents were female (54.7%). The results of the statistical test obtained p-value = 0.018 which means p α (0.05). There is a relationship between online learning and academic stress levels. It was found that online learning was more stressful than non-online learning with an OR value of 1.926, 23 of 41 non-online respondents experienced moderate stress (56.1%). A total of 32 out of 45 online respondents experienced moderate stress (71.1%). Keywords: Children's Academic Stress, Online Learning, Covid-19 ABSTRAK Pandemi Covid-19 di Indonesia mengganggu seluruh acara public dan menyebabkan penutupan sementara beberapa institusi, termasuk institusi pendidikan. Pemerintah telah menetapkan kebijakan daring. Buletin Menteri Pendidikan dan Kebudayaan, yang menyatakan bahwa pendidikan harus dilakukan secara online untuk mencegah penyebaran covid 19. Diketahui Hubungan Pembelajaran Daring Terhadap Tingkat Stress Akademik Anak Selama Pandemi Covid 19 Di Sdn 2 Kedamaian Bandar Lampung. Jenis penelitian yang digunakan adalah kuantitatif. Dengan desain penelitian yang digunakan adalah Retrospektif. Populasi penelitian ini adalah seluruh siswa/siswikelas 3 SDN 2 Kedamaian Bandar Lampung sebanyak 109 orang dengan jumlah sampel 86 responden. Dan untuk teknik sampling yang digunakan adalah Purposive Sampling. Dalam penelitian ini, kuesioner yang akan digunakan dalam penelitian ini adalah kuesioner ESSA. Penelitian ini menggunakan ananalisa data univariat dan analisa data bivariat. Analisis data menggunakan uji chi square. Hasil penelitian diketahui responden dari 86 responden didapatkan karakteristik responden. Berdasarkan usia mayoritas responden berusia 9 tahun (77,9%). Berdasarkan jenis kelamin mayoritas responden perempuan (54,7%). Hasil uji statistik diperoleh p-value = 0,018 yang berarti pα (0,05). Terdapat hubungan antara pembelajaran daring dengan tingkat stres akademik. Didapatkan pembelajaran daring lebih stres dari pada pembelajaran tidak daring dengan nilai OR 1,926 didapatkan sebanyak 23 dari 41 responden tidak daring mengalami stres sedang (56,1%). Sebanyak 32 dari 45 responden yang daring mengalami stress sedang (71,1%). Kata Kunci: Stress Akademik Anak, Pembelajaran Daring, Covid-19